Nagradne igre med mladimi na družbenem omrežju Facebook - Strašek, Nejc (Mednarodno inovativno poslovanje, 2023)
We live in a time marked by constant changes and a fast pace of life. As a society, we have become increasingly dependent on modern technologies. With the development of modern technologies, social networks are becoming more widespread, and they have become part of everyday life for teenagers. They enable young people from around the world to connect with each other and exchange their ideas and interests in an easy way. We can't imagine life without them, and there are very few individuals among us who do not have a smartphone loaded with applications such as Facebook, YouTube, Instagram, TikTok, and many others. Recently, as users of the Facebook social network, we have noticed a significant increase in the number of promotional games published by companiesfor various reasons. In this article, we present the results of a study in which we explored the popularity of the Facebook social network and promotional games among young people on this platform. We found that the majority of young people use the Facebook social network every day, primarily for socializing with friends and for participating in promotional games. Most young people access Facebook through their mobile phones. A majority of the participants have engaged in Facebook promotional games, and the key motivation for their participation is the attractive prizes offered.
Keywords: Družbena omrežja; Facebook; Igre na srečo; marketing; nagradne igre; prize games; social network